Routledge Handbook of qualitative research in sport and exercise (Routledge, 2019)
The last two decades have witnessed a proliferation of qualitative research in sport and exercise. The Routledge Handbook of Qualitative Research in Sport and Exercise is the first book to offer an in-depth survey of established and emerging qualitative methods, from conceptual first principles to practice and process.